2023
DOI: 10.1002/agg2.20395
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term responses of soil carbon, nitrogen, and microbial biomass to cover crop mixtures and monocultures

Abstract: Increasingly, cover crops are being adopted for the purpose of improving soil health, yet the timescale and magnitude by which living annual cover crops might modify soil chemical and biological aspects of soil health is not well understood. At the same time, there is growing interest among farmers in cover crop mixtures due to perceptions that species‐rich cover crop communities will enhance soil health relative to monocultures. In a field experiment in southeast New Hampshire, we investigated how groups of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Soil organic carbon was determined by potassium dichromate oxidation-external heating method, available nitrogen (AN) was determined by alkaline dissolution diffusion method, soil effective phosphorus was determined by molybdenum antimony colorimetric method, Soil available potassium was determined by flame photometric method, and pH was measured by using a mixture of soil and water (1:2.5) ( Klotz et al., 2023 ; Lin et al., 2023 ). Microbial biomass carbon (MBC) and nitrogen (MBN) were measured by chloroform fumigation-K 2 SO 4 extraction method assay ( Borah et al., 2023 ; de Souza et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil organic carbon was determined by potassium dichromate oxidation-external heating method, available nitrogen (AN) was determined by alkaline dissolution diffusion method, soil effective phosphorus was determined by molybdenum antimony colorimetric method, Soil available potassium was determined by flame photometric method, and pH was measured by using a mixture of soil and water (1:2.5) ( Klotz et al., 2023 ; Lin et al., 2023 ). Microbial biomass carbon (MBC) and nitrogen (MBN) were measured by chloroform fumigation-K 2 SO 4 extraction method assay ( Borah et al., 2023 ; de Souza et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Balanced fertilization refers to the application technology of reasonable fertilizer dosage and ratio based on the fertilizer demand characteristics of crops, soil fertilizer supply performance and fertilizer dosage to maintain nutrient balance between the proposed fertilizer dosage and ratio. For example, Zhang et al (2023) showed that N, P and K fertilizers have different effects on fruit yield and quality, of which K fertilizer is the main factor affecting yield and quality, and reasonable fertilization can significantly improve the yield and fruit quality of blueberries (Vaccinium virgatum). Yin et al (2018) found that the crop of mung bean (Vigna radiata) has a significant increase with N, P and K fertilizers.…”
Section: Introductionmentioning
confidence: 99%